Correlation between mesopore volume of carbon supports and the immobilization of laccase from Trametes versicolor for the decolorization of Acid Orange 7. (1st October 2015) - Ramírez-Montoya, Luis A.; Hernández-Montoya, Virginia; Montes-Morán, Miguel A.; Cervantes, Francisco J.
Abstract: Immobilization of laccase from Trametes versicolor was carried out using carbon supports prepared from different lignocellulosic wastes. Enzymes were immobilized by physical adsorption. Taguchi methodology was selected for the design of experiments regarding the preparation of the carbon materials, which included the use of activating agents for the promotion of mesoporosity. A good correlation between the mesopore volumes of the carbon supports and the corresponding laccase loadings attained was observed. Specifically, the chemical activation of pecan nut shell with FeCl3 led to a highly mesoporous material that also behaved as the most efficient support for the immobilization of laccase. This particular laccase/carbon support system was used as biocatalyst for the decolorization of aqueous solutions containing Acid Orange 7. Mass spectrometry coupled to a liquid chromatograph allowed us to identify the products of the dye degradation. Graphical abstract: Highlights: Immobilization of laccase has been carried out on mesoporous carbon supports. A defined correlation was observed between mesopore volume and the immobilization. Enzyme/carbon biocatalysts were used for AO7 dye solutions decolorization. Adsorption and degradation are the mechanism involved in the dye decolorization.